Pengaruh Pengembangan Karir Dan Etos Kerja Terhadap Kinerja Pegawai Pada Kantor DPRD (Dewan Perwakilan Rakyat Daerah) Di Tangerang Selatan - Amara Meyrandini; Edy Krisyanto (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract The purpose of this study was to determine the effect of career development and work ethic on employee performance at the DPRD (Regional People's Representative Council) Office in South Tangerang. The method used is quantitative. The sampling technique used slovin samples, namely 73 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are career development affects employee performance with a determination coefficient value of 34.2% and the hypothesis test obtained t count> t table or (4.553> 1.292). Work ethic has a significant effect on employee performance with a determination coefficient value of 44.8% and the hypothesis test obtained t count> t table or (8.565> 1.292). Career development and work ethic have a significant effect on employee performance with a regression equation Y = 98.536 + 0.324X1 + 0.506X2. The coefficient of determination is 48.4%, while the remaining 51.6% is influenced by other factors. The hypothesis test obtained a calculated F value > F table or (47.766 > 2.37).